PENGARUH PENERAPAN METODE GAME-BASED LEARNING TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN INFORMATIKA DI SMP NEGERI 12 PONTIANAK - Nashyfa Yasifa; Chandra Lesmana (STKIP Subang, 2026)
This study aims to determine students' learning motivation in the Informatics subject before and after the implementation of the Game-Based Learning method, as well as to identify differences in learning motivation between the class using the Game-Based Learning method and the class using the conventional method at SMP Negeri 12 Pontianak. The study employs a quantitative approach using a quasi-experimental design, specifically the Nonequivalent Control Group Design. Data collection was conducted via indirect communication using a learning motivation questionnaire. The study population consisted of all 232 Grade VII students at SMP Negeri 12 Pontianak during the 2026 academic year. The sample comprised 66 students, selected using purposive sampling: Class VII E (32 students) served as the experimental group, and Class VII A (34 students) served as the control group. Data analysis involved both descriptive and inferential statistics. The results indicate that, prior to the intervention, there was no difference in learning motivation between the experimental and control groups. Following the implementation of the Game-Based Learning method, students in the experimental group demonstrated higher learning motivation than those in the control group, with mean post-test scores of 46.42 and 35.43, respectively. The Mann-Whitney U test yielded an Asymp. Sig. (2-tailed) value of < 0.001, indicating a significant difference in learning motivation between the two groups. Thus, it can be concluded that the implementation of the Game-Based Learning method has a positive effect on students' learning motivation in the Informatics subject at SMP Negeri 12 Pontianak.